The Effectiveness of Asthma Exercise in Improving Peak Expiratory Flow in Patients with Asthma - Dian Kartikasari; Risqi Dewi Aisyah; Selmy Arnis Febgita Sugiyono; Muhammad Kamil Che Hasan (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: The prevalence of asthma increases annually. In addition to pharmacological therapy, asthma management can also be achieved through non-pharmacological therapies, including physical activity such as jogging or exercise. Exercise for asthma is beneficial for strengthening respiratory muscles and improving lung function, which can be assessed by measuring peak expiratory flow (PEF) with a peak flow meter. This study aimed to determine the effect of asthma exercise on PEF in patients with asthma. Methods: This study employed a quasi-experimental pretest-posttest control group design. A convenience sampling technique was used to select 60 individuals, who were divided into two groups: an intervention group (n=30) and a control group (n=30). The intervention group performed asthma exercise, whereas the control group received no treatment. Peak expiratory flow was measured using a peak flow meter before and after the intervention. Results: A significant difference in mean PEF values was observed between the intervention and control groups. The mean increase in PEF was higher in the intervention group than in the control group (p<0.05). Conclusion: Asthma exercises significantly increased PEF in patients with asthma. Therefore, asthma exercises can be recommended as a non-pharmacological therapy to aid asthma management.